Development of Podcast Spotify-Based Learning Media in Hörverstehen Course Level A2 - Linda Aruan; Ryan Dallion; Hafniati (Britain International for Academic Research (BIAR) Publisher, 2022)
The European Curriculum Framework or GER (Germanistische Europäische Rahmen) German language proficiency levels are divided into several groups, namely A1- A2 – B1 - B2 – C1 – C2. This requires students to master the four language skills (Speaking, Writing, Reading and Listening). Hörvestehen courses equivalent to level A2 are courses that practice listening skills. In the Hörverstehen Level A2 course, there are still many students who do not pass the listening ability (Hören). This demands that it is necessary to develop Learning Media in the Höverstehen Level A2 course. The Learning Media developed is packaged through learning media based on the Spotify Podcast, Podcast Spotify is a learning media that can be accessed anywhere, anytime and interestingly by integrating aspects of language skills according to the European Curriculum Framework or GER (Germanistische Europäische Rahmen). So, with Podcast Spotify will be able to convey the content of learning Hörverstehen Level A2 to students in the German Language Education Study Program. Therefore, the development of Spotify Podcast-Based Learning Media in the Höverstehen Level A2 course includes 6 themes, namely Leben und Lernen in Europa, Freizeit und Hobbys, Medien im Altag, Vom Land in die Stadt, Kultur erleben and Arbeitswelten. This development aims to develop learning media based on the Spotify Podcast in the Hörverstehen Level A2 Course in the German Language Education Study Program. The target of this Spotify Podcast-based learning media is to improve students' listening skills in learning German Level A2. In developing this Spotify Podcast-based learning media using the ADDIE model development method. In making Audio, the data was taken from the Studio Express A2 book and which was further developed in the form of the Spotify Audio Podcast.